PENGARUH LINGKUNGAN KERJA DAN KOMPETENSI INDIVIDU TERHADAP KINERJA PEGAWAI PADA PT. PERKEBUNAN SUMATERA UTARA - Susanto, Agus (UNIKA Santo Thomas, 2018)
The purpose of this study was to determine the influence of the working environment and competence of individuals to employee performance at PT. North Sumatera Plantations. The study population was all employees of the company as much as 157 people with a sample of 43 people. Data collection techniques used were questionnaires and documentation. The data analysis technique used is multiple linear regression equation with the F test and t. From the analysis and discussion is obtained that the working environment and competence of individuals simultaneously and partially influenced the performance of employees at PT. North Sumatera Plantations. Employee performance variation can be explained by the working environment and the individual competence of 86.5 percent.